The Armed Forces of the USA In The Asia-Pacific Region - Weeks, Stanley B. and Meconis, Charles A. (London and New York I.B. Tauris, 1999)
For over half a century, since Pearl Harbor brought the US into the Pacific War, America has been a dominant military power in Asia, challenged only by the then Soviet Union and China. This is the first unclassified account of America's military stake and current defensive and offensive capacity in Asia. It analyzes the role of US armed forces in Asia, including deterrent nuclear forces, in the context of defense policy and strategy. The possible future of US forces in the region is considered, and the book also considers the views of Asian nations on America$1 (Bs continuing presence.s
Include Index, Notes, Appendix and Biliography.
Ever since Pearl Harbor brought the USA into the Pacific War, that country has been a dominant military power in Asia, challenged only by the former Soviet Union and China. This is an account of the US military stake in Asia.
Keywords: Armed Forces--Operational Readiness -- Asia -- Military relations -- United States